Bitcoin Behavior Against Gold and Dollar Analysis Via VAR Model During Covid-19 Period - Haifa FRAD; Sihem BEN ZAKOUR; Fatemah ALGHAMDI (Communications of International Proceedings, 2021)
This paper provides insight into the transmission of shocks in the Bitcoin-Gold-dollar relationship during one-year period including COVID-19 epidemic period. The Vector autoregression (VAR) model and the generalized impulse response are used here to analyze this relationship. The result of both the Bitcoin and the Gold series exhibit cycling behavior and persistence to shocks.
Keywords: Bitcoin; Gold; Stock market; VAR; Impulse Response Function.